(untitled) (Islamic Sciences Journal, 2023)
This research deals with the researcher’s choices of al-Khatib al-Tirtashi in the Hanafi school, in which he has contradicted what was adopted by the later ones. The Book of Marriage, it is divided into five parts. The first part shows introduction the second includes marriage, third one contains prayer. Then in the fourth part it includes his choices in divorce and in the fifth his choices in transactions. And the researcher has mentioned in every issue that is approved in the school of thought. The researcher has also mentioned the opinions of the jurists in other schools of thought.